Silicon enhanced phosphorus uptake in rice under dry cultivation through root organic acid secretion and energy distribution in low phosphorus conditions - Jiang, Hao; Li, Wanchun; Jiang, Zixian; Li, Yunzhe; Shen, Xinru; Nuo, Min; Zhang, Hongcheng; Xue, Bei; Zhao, Guangxin; Tian, Ping; Yang, Meiying; Wu, Zhihai (Frontiers in Plant Science, 2025)
Dry cultivation of rice (DCR) is one of the important rice cultivation practices aimed at addressing freshwater resource shortages. However, the non-renewable nature of phosphate resources constrains agricultural development. In the context of the contradiction between rice, water, and phosphorus, there is little research on using the silicon phosphorus relationship to improve the phosphorus availability and uptake of DCR. This experiment used field soil and established five fertilization treatments: no phosphorus application, low phosphorus and normal phosphorus (0, 25, 75 kg·ha-1 P2O5) (0P, 25P, 75P), along with two silicon levels (0, 45kg·ha-1 SiO2), resulting in the treatments 0P, 0PSi, 25P, 25PSi, and 75P. The soil phosphorus components and plant phosphorus uptake were analyzed. The results showed that adding silicon to 25P increased the Olsen-P content (14.37%) by increasing Ca8-P (9.04%) and Al-P (19.31%). Additionally, root and leaf phosphorus content increased by 7.6% and 5.8%, respectively, comparable to the levels observed in the 75P treatment. On one hand, adding silicon increases malate (40.48%) and succinate (49.73%) content, enhances acid phosphatase activity, and increases the abundance of Bradyrhizobium, Paenibacillus, and Bacillus, as well as the proportion of Fusarium, forming an “organic acid microbial” activated phosphorus system. On the other hand, the addition of silicon alleviated phosphorus limitations by reducing ATP consumption in roots through a decrease in ATPase and P-ATPase content. This also minimized excessive NSC transport to roots, thereby promoting shoot growth by downregulating SUT1, SWEET11, SUS2, and CIN2. In addition to optimizing root-to-shoot ratio and providing sufficient energy, silicon addition also increases root volume and upregulates OsPT2, OsPT4, and OsPT8, thereby promoting phosphorus uptake. In summary, 25PSi optimizes the root-to-shoot ratio and promotes phosphorus conversion and uptake through organic acid, microbial, and energy pathways. Applying silicon is beneficial for the sustainable and efficient management of phosphorus in DCR.